One-stage surgery by a halo-vest to treat simultaneous double spine fractures–dislocation in a patient with ankylosing spondylitis: case report and review of literature - Wang, Liang; Qiu, Youcai; Wang, Can; Liu, Tielong; Lu, Xuhua (Frontiers in Surgery, 2024)
Study Design A case report. Background In this study, we report the outcome of one-stage surgery using a halo-vest to treat simultaneous double spine fractures–dislocation in a patient with ankylosing spondylitis (AS). Case presentation We report a case of a 57-year-old male patient with AS who sustained simultaneous double spine fractures due to a traffic accident. We performed an open approach after successful closed reduction using a halo-vest. At the 1-year follow-up, we finally achieved bone union after postoperative. At the 3-year follow-up visit, he reported a significant resolution of both cervical and back pain and had returned to his routine daily activities. Conclusion This is the first report of using a halo-vest to treat simultaneous double spine fractures–dislocation in a patient with AS. The authors included five research studies that situate this case study in the existing literature and highlight a gap in current knowledge. Based on our experience with this case and a review of the literature, one-stage surgery by a halo-vest is an effective option for the treatment of simultaneous double spine fractures–dislocation in patients with AS.